# Solve for n -7+6(-8n+8)=(-2n+5)+7

-7+6(-8n+8)=(-2n+5)+7
Simplify -7+6(-8n+8).
Simplify each term.
Apply the distributive property.
-7+6(-8n)+6⋅8=(-2n+5)+7
Multiply -8 by 6.
-7-48n+6⋅8=(-2n+5)+7
Multiply 6 by 8.
-7-48n+48=(-2n+5)+7
-7-48n+48=(-2n+5)+7
-48n+41=(-2n+5)+7
-48n+41=(-2n+5)+7
-48n+41=-2n+12
Move all terms containing n to the left side of the equation.
Add 2n to both sides of the equation.
-48n+41+2n=12
-46n+41=12
-46n+41=12
Move all terms not containing n to the right side of the equation.
Subtract 41 from both sides of the equation.
-46n=12-41
Subtract 41 from 12.
-46n=-29
-46n=-29
Divide each term by -46 and simplify.
Divide each term in -46n=-29 by -46.
-46n-46=-29-46
Cancel the common factor of -46.
Cancel the common factor.
-46n-46=-29-46
Divide n by 1.
n=-29-46
n=-29-46
Dividing two negative values results in a positive value.
n=2946
n=2946
The result can be shown in multiple forms.
Exact Form:
n=2946
Decimal Form:
n=0.63043478…
Solve for n -7+6(-8n+8)=(-2n+5)+7

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top